Kinetic Analysis of Aluminum Extraction from Ethiopian Kaolinite Using Hydrochloric Acid - Adamu Esubalew Kassa; Nurelegne Tefera Shibeshi; Belachew Zegale Tizazu (International Journal of Chemical Engineering)
The aim of this study was kinetic investigations of aluminum extraction from Ethiopian kaolinite with hydrochloric acid. The effects of extraction parameters, namely, solid-to-liquid ratio (0.05, 0.075, 0.100, and 0.125 g·mL−1), acid concentrations (2, 3, 4, and 5 M), reaction temperature (50, 60, 70, and 80°C), and time (20, 40, 60, 80, 100, 120, 140, 160, and 180 min), on yield of aluminum were investigated. The results revealed that the extraction yield of aluminum increased with increase of acid concentration, reaction temperature, and time and declined with increase of solid-to-liquid ratio. The kinetic analysis of aluminum extraction was evaluated using pseudohomogeneous, nucleation growth (Avrami), and shrinking core models. The results showed that kinetics of aluminum extraction were controlled by surface chemical reaction. The experimental results were well fitted by the shrinking core model of surface chemical reaction with first-order rate. The activation energy and the preexponential factor were 25.40 kJ·mol−1 and 0.949 cm·min−1, respectively. The leached solution samples were crystallized using evaporation and concentrated hydrochloric acid pouring. The volume ratios of concentrated hydrochloric acid to the samples were from 0.30 to 0.90 (v/v). The crystallization efficiency of aluminum chloride hexahydrate crystals increased with volume of hydrochloric acid and crystallization time. The crystallization yield of aluminum chloride hexahydrate crystals reached 90%. This study’s results clearly revealed that Ethiopian kaolinite could be a promising raw material to produce aluminum chloride hexahydrate, which could be used for water treatment application.